High grade B-cell lymphoma with MYC, BCL2 and/or BCL6 rearrangements: unraveling the genetic landscape of a rare aggressive subtype of non-Hodgkin lymphoma. Issue 6 (12th May 2022) - Ferrari, Anna; Arniani, Silvia; Crescenzi, Barbara; Ascani, Stefano; Flenghi, Leonardo; Pierini, Valentina; Moretti, Martina; Beacci, Donatella; Romoli, Silvia; Bardelli, Valentina; Calistri, Daniele; Martinelli, Giovanni; et al.
Abstract: High-grade B-cell lymphoma with MYC and BCL2 and/or BCL6 rearrangements (DH/TH-HGBL) still miss an in-depth genomic characterization. To identify accompanying genetic events, we performed a pilot study on 7 cases by applying DNA microarray and targeted NGS sequencing. Interestingly, the genetic background of DH/TH-HGBL is largely overlapping with that of other high-grade/poor prognosis lymphomas. Namely, copy number abnormalities were trisomy of chromosome 7 and chromosome 8q gain, encompassing MYC . Among gene variants, those affecting transcription factors ( MYC, FOXO1 ), epigenetic modulators ( KMT2D, EZH2 and CREEBP ), and anti-apoptotic gene ( BCL2 ), were recurrent. MYC and BCL2 were mutated in 3 and 5 cases, respectively. In addition, mutations of FOXO1, previously reported in Diffuse Large B-Cell Lymphomas, were also detected. Clarifying the genomic background of this subset of high-risk lymphomas will pave the way for the clinical use of new biomarkers to: (1) monitor treatment response and; (2) consider alternative targeted therapies.